Exploring impact of digital economy on sustainable urban development by panel data of 30 underdeveloped cities in China - Xiao-ping Bai; Qian-qian Shen (Scientific Reports)
Abstract How the digital economy affects sustainable urban development is a worthwhile research problem. Based on the panel data of 30 underdeveloped cities in China from 2011–2020, the Super-SBM model and dynamic QCA (Qualitative Comparative Analysis) method were combined to analyze the complex relationship between the digital economy and sustainable urban development. From the configuration perspective, exploring how to use the digital economy to enhance the green development level of some underdeveloped cities in northwest China is of great significance for filling this gap, establishing a cross-city green coordinated development mechanism, and formulating sustainable development policies for urban management departments. It has been found that individual digital economy elements are not necessary to enhance the level of sustainable urban development. There exist three different models for achieving green and high-quality development: high penetration effect, high scale-penetration effect, and high scale effect. For the high penetration effect model, policies promoting the development of high digital industries, high levels of economic development, a high degree of openness to the outside world, and non-high industrial structures, can be made as core conditions, with digital infrastructure construction as auxiliary conditions to fully generate high green development efficiency. For the large-scale penetration effect model, policies promoting the development of high digital industries, high digital infrastructure, high digital finance, high economic development level, high industrial structure, and non-high technique progress can generate high green development efficiency. For the large-scale effect model, policies promoting the development of non-high digital industries, high digital finance, high degree of openness to the outside world, high industrial structure, and non-high technique progress can be made as core conditions, with economic development level as auxiliary conditions, can fully generate high green development efficiency.